Factors affecting beef and plant-based protein consumption - Taylor, Hannah (Kansas State University, 2021)
Alternative protein options have been gaining popularity, motivated by increasing concerns over environmental sustainability and animal welfare. The growth in plant-based protein consumption has led to questions about how these new products might affect the beef industry. Using survey data from the Meat Demand Monitor, I evaluate factors that affect the consumption of beef and plant-based proteins and project how changing demographics might affect future protein consumption. The results show that consumption of plant-based protein and beef are not exclusive from one another. Additionally, growth in plant-based proteins need not come at the expense of the beef industry. As the U.S. population increases, expanding protein demand allows room for both beef and plant-based protein consumption to grow.
Keywords: Meat demand; Beef consumption; Plant-based proteins